What Provisions Do Orthopaedic Programs Make for Maternity, Paternity, and Adoption Leave?. Issue 9 (September 2016) - Weiss, Jennifer; Teuscher, David
Abstract: Background: The process of choosing medical specialty and residency programs is multifaceted. Today's generation of medical students may have an increased interest in work‐life balance and time with their families. In considering this factor, medical students may be influenced by policy regarding maternity, paternity, and adoption leave during residency and fellowship training. Current policy among orthopaedic programs regarding maternity, paternity, and adoption leave is not well described. To understand the influence these policies may have on the choices that medical students make in choosing their specialty, the policies must first be better understood. Questions/purposes: (1) What proportion of orthopaedic programs have formal or unwritten policies regarding maternity, paternity, and adoptive leave? (2) What are the provisions for time away, allotment of time, and makeup options for trainees who take leave? (3) What proportion of orthopaedic programs report utilization of leave, and what proportions of leave are for maternity, paternity, or adoptive reasons? Methods: Accredited programs in orthopaedic surgery were identified through the Council of Orthopedic Residency Directors within the American Orthopaedic Association. Current program directors of these accredited programs were surveyed. The survey was emailed to 144 program directors, of which 141 emails were delivered. Responses were received from 45 program directors, representing 31% of programs. The survey focused on maternity, paternity, and adoptive leave, and it consisted of questions designed to explore program policies (formal, unwritten, no policy, or in development), time considerations (amount allowed, allocation of time away, and makeup requirements), and utilization (trainees who took leave and type of leave used). Results: Most respondents have maternity leave policy (formal: 36 of 45 [80%]; unwritten: 17 of 45 [38%]). Sixteen programs (16 of 45 [36%]) reported having both a formal and an unwritten maternity leave policy. Less than half of the programs have paternity leave policy (formal: 22 of 45 [49%]; unwritten: 19 of 45 [42%]), and fewer programs have adoption leave policy (formal: eight of 45 [18%]; unwritten: 11 of 45 [24%]). For programs that have formal or unwritten policies, most programs allow 4 to 6 weeks off (26 of 43 [60%]) with nearly half of programs allocating leave as paid time off (15 of 37 programs [41%]) and nearly half of programs requiring makeup time (17 of 37 [46%]). Many programs reported no utilization of leave by trainees (23 of 36 [61%]); many programs reported utilization by three or fewer residents (11 of 13 [85%]); and among residents who took leave, maternity was the most common reason (maternity: 22 of 36 [61%]; paternity: 11 of 36 [31%]; adoption: three of 36 [8%]). Conclusions: This study highlights the lack of uniformity among orthopaedic surgery residency and training programs regarding approach to maternity, paternity, and adoption leave. Discussion among program directors, perhaps facilitated by the Council of Orthopedic Residency Directors within the American Orthopaedic Association, to align the programs' policy in this arena may provide more transparent and uniform policy for trainees in orthopaedic surgery.